Discussing with Juan Auz. Fighting climate change in the name of rights. What lessons from the Global South? - Palombino, Giacomo (EUNOMÍA. Revista en Cultura de la Legalidad, 2024)
Climate litigation is one of the central topics of contemporary legal debate, not least because it forces us to think about classic categories, but in terms of new perspectives. The paper by Juan Auz Vaca, which we comment in this discussion section, offers very interesting ideas for reflection in this regard. My contribution, then, attempts to follow the thread exposed in his publication, above all in the direction of encouraging a discussion around some elements that I consider relevant.
Keywords: Climate litigation; rights protection; anthropocentrism; ecocentrism; constitutionalism